2022
DOI: 10.1002/acr.24534
|View full text |Cite
|
Sign up to set email alerts
|

“It's Not My Knee”: Understanding Ongoing Pain and Discomfort After Total Knee Replacement Through Re‐Embodiment

Abstract: Objective. Up to 20% of people who undergo total knee replacement surgery have ongoing pain and discomfort. The aim of this study was to understand what role the concepts of embodiment (of both having a body and experiencing the world through one's body) and incorporation (integrating something into one's body) might have in understanding experiences of pain and discomfort after total knee replacement.Methods. We conducted semistructured interviews with 34 people who had received total knee replacement at eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
(66 reference statements)
0
11
0
Order By: Relevance
“…Chronic pain despite joint replacement is not uncommon, affecting approximately 10% of patients after total hip replacement and 20% of patients after total knee replacement (Wylde, 2015). The related emotion reported in literature is fear (Unver, 2014), altogether with withdrawal and depression (Moore, 2022). Psychological and structural factors interact exacerbating pain perception (Pan, 2018, Nwanko 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic pain despite joint replacement is not uncommon, affecting approximately 10% of patients after total hip replacement and 20% of patients after total knee replacement (Wylde, 2015). The related emotion reported in literature is fear (Unver, 2014), altogether with withdrawal and depression (Moore, 2022). Psychological and structural factors interact exacerbating pain perception (Pan, 2018, Nwanko 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic pain despite joint replacement is not uncommon, affecting approximately 10% of patients after total hip replacement and 20% of patients after total knee replacement 34 . The related emotion reported in scientific literature is fear 14 , altogether with withdrawal and depression 15 . Psychological and structural factors interact exacerbating pain perception 16 , 17 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Specific emotional patterns emerged to relate to different musculoskeletal degenerative diseases [9][10][11][12][13][14][15][16][17] ; the emotional content of external sources of information can complement rather than mirror users' , in a nonstraightforward complex system, in analogy with the counterintuitive role of sadness in the pleasure elicited by OPEN 1 Humanitas Gradenigo Hospital, Turin, Italy. 2 Imparamare Ong, Asti, Italy.…”
mentioning
confidence: 99%
“…Patients with chronic musculoskeletal pain sufer from not only pain but also abnormal body perception [1][2][3][4][5][6][7][8]. A previous study reported that cast immobilization immediately after a fracture or tissue injury caused abnormal body perception in addition to limiting physical function, such as joint contracture and muscle weakness [9].…”
Section: Introductionmentioning
confidence: 99%
“…Tis abnormal perception has been described by patients in clinical settings in various ways, such as "it does not feel like my hand," and "I feel uncomfortable or strange about my hand" [10]. In several other studies, Patients with chronic musculoskeletal pain described their experience in the following ways: "I feel like my body is lead," "I feel like my body is constricted," "I feel like my body is swollen," and "I feel discomfort in my body" [1,8,11,12]. Such abnormal perception is thought to be caused by incongruence between motor intentions and sensory feedback [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%